Association of a single nucleotide polymorphism in the TLR2 gene (rs3804099), but not in the TLR4 gene (rs4986790), with Helicobacter pylori infection and peptic ulcer - Ehsan Mirkamandar; Maryam Nemati; Mohammad Mehdi Hayatbakhsh; Arezu Bassagh; Arezu Khosravimashizi; Abdollah Jafarzadeh (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Toll-like receptors (TLRs), particularly TLR2 and TLR4, take part in elicitation of immune responses against Helicobacter pylori (H. pylori). This study aimed to investigate the relationship between single nucleotide polymorphisms (SNP) rs3804099 in the TLR2 gene and rs4986790 in the TLR4 gene with H. pylori infection and peptic ulcer (PU). Materials and Methods: Blood specimens were obtained from 350 individuals, including 100 H. pylori-infected patients with PU, 125 H. pylori-infected asymptomatic subjects (AS), and 125 non-infected healthy subjects (NHS). The DNA was extracted, and the SNPs were determined using ARMS-PCR method. Results: The frequency of CT genotype at TLR2 SNP rs3804099 in both the PU and AS groups was significantly higher than in the NHS group (p<0.05). In total H. pylori-infected individuals (PU+AS), the frequency of the CT genotype at rs3804099 was also significantly higher than in the NHS group (p<0.005). The frequency of the CC genotype at rs3804099 in PU+AS was markedly lower than in the NHS group (p=0.066). PU patients carried CT genotype more frequently than total healthy individuals (AS+NHS) (p<0.03). The distribution of the TT genotype was lower, whereas the frequency of the CT genotype was higher in AS individuals infected with CagA+ strains than those infected with CagA- strains (p<0.03). No significant differences were found among the PU, AS, and NHS groups regarding the genetic differences at rs4986790 in the TLR4 gene. Conclusion: These results provide evidence regarding the association of the rs3804099 in the TLR2 gene with H. pylori infection and PU. The rs3804099 may affect vulnerability to H. pylori infection, particularly to CagA+ strains of bacteria. Cite this article as: Mirkamandar E, Nemati M, Hayatbakhsh MM, Bassagh A, Khosravimashizi A, Jafarzadeh A. Association of a single nucleotide polymorphism in the TLR2 gene (rs3804099), but not in the TLR4 gene (rs4986790), with Helicobacter pylori infection and peptic ulcer. Turk J Gastroenterol 2018; 29: 283-91.